2014
DOI: 10.1111/2049-632x.12180
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking the host and its microenvironmentin vitrofor studying mucosal infections byPseudomonas aeruginosa

Abstract: Why is a healthy person protected from Pseudomonas aeruginosa infections, while individuals with cystic fibrosis or damaged epithelium are particularly susceptible to this opportunistic pathogen? In order to address this question, it is essential to thoroughly understand the dynamic interplay between the host microenvironment and P. aeruginosa. Therefore, using modeI systems that represent key aspects of human mucosal tissues in health and disease allows recreating in vivo host-pathogen interactions in a physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 222 publications
(344 reference statements)
2
30
0
Order By: Relevance
“…In line with our results for C. jejuni and the tissue-engineered 3D model, various other 3D models including those cultured in the rotating wall vessel bioreactor (RWV) or organs-on-achip are promising new tools for infection research and have been applied to study a variety of pathogens, such as S. Typhimurium, Pseudomonas aeruginosa, or Mycobacterium tuberculosis [84][85][86][87][88][89]. For example, 3D models grown in the RWV successfully recapitulated infection outcomes, such as SPI-1 independent invasion of host cells by S. Typhimurium [84], as previously observed in vivo [90].…”
Section: Discussionsupporting
confidence: 74%
“…In line with our results for C. jejuni and the tissue-engineered 3D model, various other 3D models including those cultured in the rotating wall vessel bioreactor (RWV) or organs-on-achip are promising new tools for infection research and have been applied to study a variety of pathogens, such as S. Typhimurium, Pseudomonas aeruginosa, or Mycobacterium tuberculosis [84][85][86][87][88][89]. For example, 3D models grown in the RWV successfully recapitulated infection outcomes, such as SPI-1 independent invasion of host cells by S. Typhimurium [84], as previously observed in vivo [90].…”
Section: Discussionsupporting
confidence: 74%
“…NASA suspension culture techniques reverse much of the problematic de-differentiation of cells observed during other forms of tissue culture (35–38). The technology has been applied broadly to diverse cell types including cancer cells, prostate, kidney, micro-organisms, biofilms, and plants, to name a few (36,39,40). …”
Section: Is There a Space-based Technology Solution To The Clinical Dmentioning
confidence: 99%
“…In addition to repopulation assays, it has also been suggested that recellularized acellular scaffolds could also be used for studying infectious diseases (Crabbé et al 2014 ) and used as models for cancer development (Mishra et al 2012 ). Thus, studies to date have likely only begun to demonstrate the utility of acellular tissue as ex vivo models of disease which more closely recapitulate in vivo microenvironments than traditional in vitro setups.…”
Section: Acellular Lungs As Ex Vivo Models Of Diseasementioning
confidence: 99%